Biotriborheology of Shea Butter Solid Lipid Nanoparticles in a topical cream. (April 2021) - Avilés-Castrillo, J.I.; Quintanar-Guerrero, D.; Aguilar-Pérez, K.M.; Medina, D.I.
Abstract: Solid lipid nanoparticles (SLNs) provide excellent biocompatibility and efficient encapsulation as pharmaceutical delivery systems. In this study, shea butter SLNs were synthesized by the hot homogenization technique, with excellent stability. The penetration capacity of nanoparticles was validated by atomic force microscopy, scanning electron microscopy, differential scanning calorimetry, dynamic light scattering, using zeta potential measurements, and confocal microscopy. Triborheological tests such as viscosity shear rate profiling, normal stress profiling and sliding speed sweeping were conducted to identify and quantify the impact of SLNs in topical formulations. We found that the SLNs had a lower coefficient of friction than the bulk lipids owing to a more stable lipid layer formation of the SLNs. SLNs in topical formulations have potential applications in cosmetics such as anti-aging agents owing to their emollient, occlusion, antioxidant and anti-inflammatory properties. Graphical abstract: Image 1 Highlights: Shea Butter Solid Lipid Nanoparticles (SLNs) present lower Friction Coefficient than bulk material. Shea Butter SLNs improve lubrication behavior in base cream to have better cosmetic properties. The mechanism of lubrication of SLNs is protective film. Biotriborheology and confocal microscopy confirm the penetration of SLNs through skin and lipid layer formation. Biotriborheology indicates that the best axial force to apply base cream with Shea Butter SLNs is 1 N.